2019
DOI: 10.1021/acs.chemrev.9b00023
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Induced Nanoparticle Phase Behavior, Property, and Applications

Abstract: Nanoparticle (NP) high pressure behavior has been extensively studied over the years. In this review, we summarize recent progress on the studies of pressure induced NP phase behavior, property, and applications. This review starts with a brief overview of high pressure characterization techniques, coupled with synchrotron X-ray scattering, Raman, fluorescence, and absorption. Then, we survey the pressure induced phase transition of NP atomic crystal structure including size dependent phase transition, amorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(148 citation statements)
references
References 303 publications
(757 reference statements)
4
138
3
Order By: Relevance
“…Pressure, as a clean tuning “knob”, can effectively modulate the distortion degree and crystal structures of LDHPs without changing the chemical composition. [ 9–17 ] The efficient bandgap tuning and emission enhancement in LDHPs render the pressure a robust tool to achieve the optimization of optical properties. [ 18–20 ] However, deep insight into relationship between the distorted formation of octahedral frameworks and controllable emission enhancements of LDHPs still remained obscure as yet.…”
Section: Figurementioning
confidence: 99%
“…Pressure, as a clean tuning “knob”, can effectively modulate the distortion degree and crystal structures of LDHPs without changing the chemical composition. [ 9–17 ] The efficient bandgap tuning and emission enhancement in LDHPs render the pressure a robust tool to achieve the optimization of optical properties. [ 18–20 ] However, deep insight into relationship between the distorted formation of octahedral frameworks and controllable emission enhancements of LDHPs still remained obscure as yet.…”
Section: Figurementioning
confidence: 99%
“…High-pressure research on nanomaterials has brought about widely attention because of the emergence of many exceptional behaviors on nanocrystals under high pressure. [1][2][3][4][5][6] Previous research has revealed that the high-pressure behaviors of nanomaterials are significantly different from that of the bulk counterparts, in which the nanosize and the shape have been considered to be crucial factors. [7][8][9] Recently, the effects of the nanosize and morphology on the phase transitions have been observed in several nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…16). There have been some interesting studies that show new nanostructures, such as gold or CdSe nanowires can be synthesized by compression of their small nanoparticles [32][33][34] . In this work, we found that large area of compact and fused morphology changes appears in nanosheet assemblies upon mechanical compression.…”
Section: Resultsmentioning
confidence: 99%